Philosophical Education in Coordinates of Science - V. A. Yakovlev (Высшее образование в России)
The article justifies the inextricable interconnectedness and creative interaction of philosophy, science and education in the course of their historical development. The article focuses on the problem of teaching the course of history and philosophy of science (HFS) in terms of formation of critical creative thinking of the future scientist. The author’s teaching experience of the HFS course at the Faculty of Physics of Moscow State University named after M.V. Lomonosov is described. It is substantiated that the term «science» should be defined, first of all, as a block of natural-science disciplines. The presentation in the lecture course and further elaboration in seminars of genesis and the development of these programmes form the basis for doctoral students’ understanding of the unity and continuity of scientific knowledge in history. The article presents a comparative analysis of positive and negative assessments by scientists of the relationship between philosophy and science. Special attention is paid to the students’ understanding of the method of scientific discussion and the concept of «truth». Examples from both the history of philosophy and history of science are used. It has been shown that discussions alone cannot lead to the discovery of the truth, but they are necessary to further stimulate the development of science and theoretical thinking. The discussions at seminars contribute to the development of communicative practices of future researchers. It cannot be accepted that classical lectures are becoming anachronistic nowadays. The author argues that a classical lecture is not just a text and a content. What is important, first of all, is a direct contact with audience, which entails so-called body language including mimics, gestures and intonations. This language plays an important role from a psychological point of view. It is proposed that discussions among educators and practitioners be organized on the basis of a permanent methodological seminar to discuss the basic issues of the HFS course.